A STUDY ON THE ABILITY OF THE THIRD YEAR STUDENTS OF THE ENGLISH STUDY PROGRAM OF FKIP RIAU UNIVERSITY IN WRITING A NARRATIVE ESSAY - Dinna Auliya; Afrianto '; Masyhur ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The objective of this study is to find out the level ability of the third year students of the English Study Program of FKIP Riau University in writing a narrative essay. The research design is a descriptive quantitative research. There are 25 students chosen as the samples of this research. The instrument of the research was a written test that was assessed by the three raters by referring Heaton’s scoring guide and Harris’ measurement. It was found that 3 students (12%) were in excellent level, 12 students (48%) were in good level, 9 students (36%) were in mediocre level, 1 student (4%) was in poor level, and there was no student in very poor level. It can be concluded that the students can write a narrative essay with the average score was 65,15. Overall, the students’ problems were dominated in category of language usage. Most of students made a lot mistakes in using tenses and constructing sentences.Key Words: Students, Ability, Writing, Narrative Essay